Catalyst and method for preparing a compound using the same
Patent Information
- Application Number
- KR1020227021517
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-10
- Filing Date
- 2021-01-08
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-01-08
Smart Images

Figure 112022065843835-PCT00004_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a catalyst, a method for manufacturing a compound using the same, and a compound. Background Technology
[0002] Methods for producing corresponding unsaturated aldehydes and unsaturated carboxylic acids using propylene, isobutylene, t-butyl alcohol, etc. as raw materials, or gas-phase contact oxidation methods for producing 1,3-butadiene from butenes, are widely practiced industrially.
[0003] In particular, regarding methods for producing corresponding unsaturated aldehydes and unsaturated carboxylic acids using propylene, isobutylene, t-butyl alcohol, etc. as raw materials, many reports have been made as means to improve the yield or catalytic activity thereof (e.g., Patent Document 1, etc.).
[0004] Among them, Patent Document 2 describes that a catalyst exhibiting high yield and high selectivity is obtained by controlling the ratio Ri = Pi / Ph, which is the ratio of the intensity Pi of the diffraction peak (i) of β-Bi2Mo2O9 appearing at 2θ = 27.76 ± 0.1° to the intensity Ph of the diffraction peak (h) of CoMoO4 appearing at 2θ = 26.5 ± 0.1° in the X-ray diffraction pattern using Cu-Kα rays of the catalytic active component, to a range of 0.4 or higher and 2.0 or lower.
[0005] Patent Document 3 states that catalytic performance, such as catalytic activity and selectivity, can be improved by controlling the degree of crystallization T, which is measured by X-ray diffraction analysis of the catalytic active component using Cu-Kα rays, to a range of 4% to 18%.
[0006] In addition, Patent Document 4 describes Bi appearing at 2θ = 27.4°±0.2° with respect to the intensity Pc of the diffraction peak (c) of the CoMoO4 phase appearing at 2θ = 26.4°±0.2° 10 Mo3O 24It is stated that in an oxide catalyst in which the ratio of Pa to the intensity of the diffraction peak (a) of the phase Ri = Pa / Pc is 0.2 ≤ Ri ≤ 1.0, the increase in activity over time in the reaction is small, and unsaturated aldehydes can be produced in high yield.
[0007] On the other hand, further improvements in yield and catalyst activity are required in the production of corresponding unsaturated aldehydes and / or unsaturated carboxylic acids by partial oxidation reactions of propylene, isobutylene, t-butyl alcohol, etc., or in the production of conjugated dienes by oxidative dehydrogenation reactions of butenes. For example, the yield of the target product is influenced by the amount of propylene, isobutylene, t-butyl alcohol, and butenes, etc., required for production, and thus has a significant impact on production costs. Furthermore, catalyst activity influences the reaction bath temperature when producing the target product; if a catalyst with low activity is used, the reaction bath temperature must be raised to maintain the quantity of the target product. Consequently, the catalyst is subjected to thermal stress, which may lead to a decrease in selectivity or yield and a reduction in catalyst lifespan.
[0008] Particularly regarding catalyst lifespan, the relationship between the catalyst's physical properties or their changes over time and the catalyst's lifespan was unclear. When using catalysts to produce unsaturated aldehydes, unsaturated carboxylic acids, or conjugated dienes with high yield and / or high selectivity, it was not clear which catalyst characteristics to use and by what indicators to manage them. Prior art literature
[0009] International Publication No. 2016 / 136882, Japanese Published Patent Application No. 2017-024009, International Publication No. 2010 / 038677, Japanese Published Patent Application No. 2018-140326 The problem to be solved
[0010] The present invention proposes a catalyst with high catalytic activity and selectivity of the target product, which is used as a catalyst in a method for producing corresponding unsaturated aldehydes or unsaturated carboxylic acids using propylene, isobutylene, t-butyl alcohol, etc. as raw materials, or in a gas-phase contact oxidation method for producing 1,3-butadiene from butenes. Furthermore, by using the catalyst of the present invention, long-term operation of the gas-phase contact oxidation method becomes possible safely, stably, and at low cost. means of solving the problem
[0011] Conventionally, there have been cases where the reduction in selectivity during a reaction due to the type of catalyst was a problem, and the reason for this was unknown, but the present invention was arrived at by evaluating the catalyst after the reaction. That is, the characteristic that the rate of change of the peak intensity of 2θ = 25.3 ± 0.2° after the reaction is small leads to the suppression of the reduction in selectivity, which was discovered for the first time by the inventors.
[0012] That is, the present invention relates to the following 1) to 11).
[0013] 1)
[0014] A catalyst containing molybdenum, bismuth, and cobalt as essential components, wherein the rate of change (Q1) per 1,000 hours of reaction time represented by the following formulas (1) to (4) is 16 or less for the peak intensity of 2θ = 25.3 ± 0.2° in the X-ray diffraction pattern obtained using CuKα rays as an X-ray source.
[0015] Q1={(U1 / F1-1)×100} / T×1000···(1)
[0016] F1=(peak intensity value of catalyst before oxidation reaction at 2θ=25.3±0.2°)÷(peak intensity value of catalyst before oxidation reaction at 2θ=26.5±0.2°)×100···(2)
[0017] U1=(peak intensity value of catalyst after oxidation reaction at 2θ=25.3±0.2°)÷(peak intensity value of catalyst after oxidation reaction at 2θ=26.5±0.2°)×100···(3)
[0018] T = Time taken for oxidation reaction (hr)···(4)
[0019] 2)
[0020] A catalyst described in 1) having a change amount (D1) per 1000 hours of reaction time represented by the following formula (5) and the above formulas (2) to (4), with respect to the peak intensity of 2θ = 25.3±0.2° in the X-ray diffraction pattern obtained using CuKα rays as an X-ray source, which is 4.1 or less.
[0021] D1=(U1-F1) / T×1000···(5)
[0022] 3)
[0023] A catalyst described in 1) or 2), wherein the composition of the catalytic active component is represented by the following formula (A).
[0024] Mo a1 Bi b1 Ni c1 Co d1 Fe e1 X f1 Y g1 Z h1 O i1 ···(A)
[0025] (In the formula, Mo, Bi, Ni, Co, and Fe represent molybdenum, bismuth, nickel, cobalt, and iron, respectively; X represents at least one element selected from tungsten, antimony, tin, zinc, chromium, manganese, magnesium, silicon, aluminum, cerium, and titanium; Y represents at least one element selected from sodium, potassium, cesium, rubidium, and thallium; Z represents at least one element belonging to Groups 1 through 16 of the periodic table and selected from elements other than Mo, Bi, Ni, Co, Fe, X, and Y; a1, b1, c1, d1, e1, f1, g1, h1, and i1 represent the number of atoms of molybdenum, bismuth, nickel, cobalt, iron, X, Y, Z, and oxygen, respectively; and when a1 = 12, 0 < b1 ≤ 7, 0 ≤ c1 ≤ 10, 0 < d1 ≤ 10, 0<c1+d1≤20, 0≤e1≤5, 0≤f1≤2, 0≤g1≤3, 0≤h1≤5, and i1=a value determined by the oxidation state of each element.
[0026] 4)
[0027] A catalyst described in any one of claims 1) to 3), which is a catalyst in which a catalytic active component is supported on an inert carrier.
[0028] 5)
[0029] The catalyst described in 4), wherein the inert carrier is silica, alumina, or a mixture thereof.
[0030] 6)
[0031] A catalyst described in any one of claims 1) to 5), which is a catalyst for the production of at least one type of unsaturated aldehyde compound, unsaturated carboxylic acid compound, and conjugated diene.
[0032] 7)
[0033] A method for producing at least one type of unsaturated aldehyde compound, unsaturated carboxylic acid compound, and conjugated diene using a catalyst described in any one of claims 1 to 6).
[0034] 8)
[0035] A manufacturing method described in 7), wherein the unsaturated aldehyde compound is acrolein, the unsaturated carboxylic acid compound is acrylic acid, and the conjugated diene is 1,3-butadiene.
[0036] 9)
[0037] An unsaturated aldehyde compound, an unsaturated carboxylic acid compound, or a conjugated diene produced using a catalyst described in any one of claims 1 to 6).
[0038] 10)
[0039] A method for producing at least one type of unsaturated aldehyde compound, unsaturated carboxylic acid compound, and conjugated diene, wherein the change rate (Q4) per 1000 hours of reaction time represented by the following formulas (14) to (17) is 16 or less, with respect to the peak intensity of 2θ = 25.3±0.2° in the X-ray diffraction pattern obtained using the CuKα rays of said catalyst as an X-ray source.
[0040] Q4={(U4 / F4-1)×100} / T×1000···(14)
[0041] U4=(peak intensity value of catalyst at 2θ=25.3±0.2° after oxidation reaction)÷(peak intensity value of catalyst at 2θ=26.5±0.2° after oxidation reaction)×100···(15)
[0042] F4=(peak intensity value of catalyst before oxidation reaction at 2θ=25.3±0.2°)÷(peak intensity value of catalyst before oxidation reaction at 2θ=26.5±0.2°)×100···(16)
[0043] T = Time taken for oxidation reaction (hr)···(17)
[0044] 11)
[0045] A method for producing at least one of the unsaturated aldehyde compound, unsaturated carboxylic acid compound and conjugated diene described in 10), wherein the change amount (D4) per 1000 hours of reaction time represented by the following formula (18) is 4.1 or less.
[0046] D4=(U4-F4) / T×1000···(18) Effects of the invention
[0047] The catalyst of the present invention is effective in maintaining high selectivity and improving yield in gas-phase catalytic oxidation reactions or gas-phase catalytic dehydrogenation reactions. It is particularly useful when producing corresponding unsaturated aldehydes or unsaturated carboxylic acids using propylene, isobutylene, t-butyl alcohol, etc. as raw materials. Brief explanation of the drawing
[0048] Figure 1 is a diagram showing the X-ray diffraction pattern of the catalyst (catalyst 3-1) of Example 3. Figure 2 is a diagram showing the X-ray diffraction pattern of the catalyst of Example 3 (catalyst 3-2). Figure 3 is a diagram showing the X-ray diffraction pattern of the catalyst (catalyst 4-1) of Comparative Example 1. Figure 4 is a diagram showing the X-ray diffraction pattern of the catalyst (catalyst 4-2) of Comparative Example 1. Specific details for implementing the invention
[0049] (Form for carrying out the invention)
[0050] Embodiments of the present invention will be described below. Additionally, in this specification, the gas-phase contact oxidation reaction and the gas-phase contact oxidative dehydrogenation reaction may be collectively referred to simply as the oxidation reaction.
[0051] [Regarding the rate of change (Q1) per 1,000 hours of response time of the peak intensity at 2θ = 25.3 ± 0.2° in the X-ray diffraction pattern]
[0052] The catalyst of the present embodiment is characterized by a change rate (Q1) per 1000 hours of reaction time represented by the following formulas (1) to (4), with respect to the peak intensity of 2θ = 25.3±0.2° in the X-ray diffraction pattern obtained using CuKα rays as an X-ray source.
[0053] Q1={(U1 / F1-1)×100} / T×1000···(1)
[0054] F1=(peak intensity value of catalyst before oxidation reaction at 2θ=25.3±0.2°)÷(peak intensity value of catalyst before oxidation reaction at 2θ=26.5±0.2°)×100···(2)
[0055] U1=(peak intensity value of catalyst after oxidation reaction at 2θ=25.3±0.2°)÷(peak intensity value of catalyst after oxidation reaction at 2θ=26.5±0.2°)×100···(3)
[0056] T = Time taken for oxidation reaction (hr)···(4)
[0057] In addition, the peak intensity (F1) and peak intensity (U1) are obtained by normalizing the peak intensity shown at 2θ = 26.5 ± 0.2°, but since the rate of change (Q1) divides U1 by F1, it is practically calculated based on the value obtained as (peak intensity value of the catalyst at 2θ = 25.3 ± 0.2° after oxidation reaction) ÷ (peak intensity value of the catalyst at 2θ = 25.3 ± 0.2° before oxidation reaction).
[0058] Here, peak intensity is explained. The peak intensity at 2θ = 25.3±0.2° refers to the maximum value of the signal observed within the range of 2θ = 25.3±0.2°, but its essence represents the peak height of the crystalline phase of α-CoMoO4. Additionally, the peak intensity at 2θ = 26.5±0.2° refers to the maximum value of the signal observed within the range of 2θ = 26.5±0.2°, but its essence represents the peak height of the crystalline phase of β-CoMoO4. That is, the present invention is based on the discovery that when the rate of change (Q1) per 1000 hours of reaction time due to oxidation reaction between the peak intensity of the crystalline phase of α-CoMoO4 shown at 2θ = 25.3±0.2° and the peak intensity of the crystalline phase of β-CoMoO4 shown at 2θ = 26.5±0.2° is below a certain level, specifically below 16, the selectivity stabilizes.
[0059] As described below, the crystalline phase of α-CoMoO4 changes depending on the composition or preparation method of the catalyst, and its stability also changes. This can be confirmed by focusing on the rate of change (Q1) per 1,000 hours of reaction time of the peak intensity at 2θ = 25.3 ± 0.2°. The range of Q1 is 16 or less as described above, but the values more preferable as the upper limit are, in order, 15, 10, 7.0, 5.0, 2.2, 2.0, 1.5, 1.2, 1.0, 0.70, and 0.50, more preferably 0.0, even more preferably -5.0, and most preferably -7.0. In addition, a lower limit value may not be set, but the desirable values are, in order, -100, -80, -60, -40, and -20, more preferably -15, even more preferably -10, and most preferably -8.0. That is, the more desirable range as the rate of change (Q1) of peak intensity per 1000 hours of response time is set by the upper and lower limits above, for example, from -40 to 15, and most preferably from -8.0 to -7.0.
[0060] In addition, as a method for measuring the X-ray diffraction angle (2θ) of the catalyst, for example, the measurement of the X-ray diffraction angle (2θ) may be performed using Ultima IV manufactured by Rigaku Co., Ltd. under conditions of X-ray CuKα (λ = 0.154 nm), output 40 kV, 30 mA, measurement range 10 to 60°, and measurement speed 10° per minute, but is not limited thereto as long as the measurement principle is not deviated from. In addition, the peak intensity of the present embodiment is to be calculated after removing the background and halo pattern described in Patent Document 3 from the X-ray diffraction pattern before the calculation thereof. In addition, if each of the aforementioned peaks does not have a clear maximum value within the corresponding range of 2θ, or does not have a peak shape, or if there is too much noise and it is not judged to be a clear peak, the peak intensity is to be 0 in the present embodiment.
[0061] [Regarding the rate of change of other peaks in the X-ray diffraction pattern]
[0062] There are other X-ray diffraction peaks attributed to α-CoMoO4. For the peak intensity shown within the range of 2θ = 32.7 ± 0.2° in the X-ray diffraction pattern obtained using the CuKα rays of the catalyst as an X-ray source, it is preferable that the rate of change (Q2) per 1000 hours of reaction time, represented by the following equations (6) to (8) and the aforementioned equation (4), is 4.8 or less. Furthermore, since the rate of change (Q2) is calculated by dividing U2 by F2, it is substantially calculated based on the value obtained as (peak intensity value of 2θ = 32.7 ± 0.2° of the catalyst after oxidation reaction) ÷ (peak intensity value of 2θ = 32.7 ± 0.2° of the catalyst before oxidation reaction).
[0063] Q2={(U2 / F2-1)×100} / T×1000···(6)
[0064] F2=(peak intensity value of catalyst before oxidation reaction at 2θ=32.7±0.2°)÷(peak intensity value of catalyst before oxidation reaction at 2θ=26.5±0.2°)×100···(7)
[0065] U2=(peak intensity value of catalyst after oxidation reaction at 2θ=32.7±0.2°)÷(peak intensity value of catalyst after oxidation reaction at 2θ=26.5±0.2°)×100···(8)
[0066] The preferred values as the upper limit of the rate of change (Q2) of peak intensity per 1,000 hours of response time shown within the range of 2θ = 32.7 ± 0.2° are, in order, 4.0, 3.0, 2.7, 2.5, 2.0, 1.8, and 1.6; more preferably, 1.0; even more preferably, 0.0; and most preferably, -10. In addition, the lower limit may not be set, but the preferred values are, in order, -100, -80, -60, and -40; more preferably, -20; even more preferably, -15; and most preferably, -14. That is, the more preferred range as the rate of change (Q2) of peak intensity is set by the upper and lower limits above, for example, from -40 to 4.0, and most preferably from -14 to -10.
[0067] In addition to the X-ray diffraction peak attributed to the above-mentioned α-CoMoO4, for the peak intensity shown within the range of 2θ = 47.4±0.2° in the X-ray diffraction pattern obtained using the CuKα rays of the catalyst as an X-ray source, it is preferable that the rate of change (Q3) per 1000 hours of reaction time, represented by the following equations (9) to (11) and the aforementioned equation (4), is 8.7 or less. Furthermore, since the rate of change (Q3) is calculated by dividing U3 by F3, it is substantially calculated based on the value obtained as (peak intensity value of 2θ = 47.4±0.2° of the catalyst after oxidation reaction) ÷ (peak intensity value of 2θ = 47.4±0.2° of the catalyst before oxidation reaction).
[0068] Q3={(U3 / F3-1)×100} / T×1000···(9)
[0069] F3=(peak intensity value of catalyst before oxidation reaction at 2θ=47.4±0.2°)÷(peak intensity value of catalyst before oxidation reaction at 2θ=26.5±0.2°)×100···(10)
[0070] U3=(peak intensity value of catalyst at 2θ=47.4±0.2° after oxidation reaction)÷(peak intensity value of catalyst at 2θ=26.5±0.2° after oxidation reaction)×100···(11)
[0071] The preferred values as the upper limit of the rate of change (Q3) of peak intensity per 1,000 hours of response time shown within the range of 2θ = 47.4 ± 0.2° are, in order, 8.0, 3.0, 2.2, 2.0, 1.7, and 1.5; more preferably, 1.0; even more preferably, 0.5; and most preferably, 0.3. In addition, the lower limit may not be set, but the preferred values are, in order, -100, -80, -60, -40, -20, and -10; more preferably, -5.0; even more preferably, -1.0; and most preferably, 0.0. That is, the more preferred range as the rate of change (Q3) of peak intensity is set by the upper and lower limits above, for example, from -40 to 8.0, and most preferably from 0.0 to 0.3.
[0072] [Regarding the change in peak intensity of 2θ = 25.3 ± 0.2° in the X-ray diffraction pattern per 1,000 hours of response time (D1)]
[0073] The catalyst of the present embodiment is preferably such that, with respect to the peak intensity of 2θ = 25.3±0.2° in the X-ray diffraction pattern obtained using CuKα rays as an X-ray source, the change amount (D1) per 1000 hours of reaction time represented by the following formula (5) and the above formulas (2) to (4) is 4.1 or less.
[0074] D1=(U1-F1) / T×1000···(5)
[0075] This is based on the discovery that when the change amount (D1) per 1000 hours of reaction time due to the oxidation reaction of the peak intensity of 2θ = 25.3±0.2° relative to the peak intensity of 2θ = 26.5±0.2° is below a certain level, specifically when it is small, such as 4.1 or less, the selectivity stabilizes.
[0076] As described below, the crystalline phase of α-CoMoO4 changes depending on the composition or preparation method of the catalyst, and its stability also changes. This can be confirmed by focusing on the change in peak intensity (D1) per 1,000 hours of reaction time, particularly at 2θ = 25.3 ± 0.2°. The range of D1 is preferably 4.1 or less as described above, but the values more preferably as the upper limit are, in order, 3.0, 2.0, 1.9, 1.5, 1.0, 0.50, 0.30, 0.20, and 0.10, more preferably 0.0, even more preferably -1.0, and most preferably -1.3. Additionally, a lower limit does not need to be set, but the preferred values are, in order, -17, -15, and -10, more preferably -5.0, even more preferably -2.0, and most preferably -1.5. That is, a more desirable range for the change amount (D1) of peak intensity per 1000 hours of reaction time is set by the upper and lower limits above, for example, -10 or more and 3.0 or less, and most preferably -1.5 or more and -1.3 or less.
[0077] [Regarding the amount of change in other peaks in the X-ray diffraction pattern]
[0078] There are other X-ray diffraction peaks attributed to α-CoMoO4, but for the peak intensity shown within the range of 2θ = 32.7 ± 0.2° in the X-ray diffraction pattern obtained using the CuKα rays of the catalyst as an X-ray source, it is desirable that the change in peak intensity (D2) per 1000 hours of reaction time, represented by the following equation (12) and the aforementioned equations (4), (7), and (8), be 0.80 or less.
[0079] D2=(U2-F2) / T×1000···(12)
[0080] The preferred upper limit value for the change amount (D2) of the peak intensity per 1,000 hours of response time shown within the range of 2θ = 32.7 ± 0.2° is, in order, 0.50, 0.30, and 0.20; more preferably, 0.10; even more preferably, 0.0; and most preferably, -1.0. Additionally, the lower limit value does not need to be set, but the preferred values are, in order, -8.7, -8.0, and -5.0; more preferably, -3.0; even more preferably, -2.0; and most preferably, -1.2. That is, the more preferred range for the change amount (D2) of the peak intensity is set by the upper and lower limits above, for example, -5.0 or higher and 0.50 or lower, and most preferably -1.2 or higher and -1.0 or lower.
[0081] In addition to the X-ray diffraction peak attributed to the above-mentioned α-CoMoO4, for the peak intensity shown within the range of 2θ = 47.4±0.2° in the X-ray diffraction pattern obtained using the CuKα rays of the catalyst as an X-ray source, it is preferable that the change amount (D3) per 1000 hours of reaction time, represented by the following equation (13) and the aforementioned equations (4), (10) and (11), is 1.2 or less.
[0082] D3=(U3-F3) / T×1000···(13)
[0083] The preferred upper limit value for the change amount (D3) of the peak intensity per 1,000 hours of response time shown within the range of 2θ = 47.4 ± 0.2° is, in order, 1.0, 0.50, 0.30, and 0.20; more preferably, 0.10; even more preferably, 0.050; and most preferably, 0.030. Additionally, the lower limit value does not need to be set, but the preferred values are, in order, -9.6, -9.0, -7.0, -5.0, -3.0, and -2.0; more preferably, -1.0; even more preferably, 0.0; and most preferably, 0.010. That is, the more preferred range for the change amount (D3) of the peak intensity is set by the upper and lower limits above, for example, from -2.0 to 1.0, and most preferably from 0.010 to 0.050.
[0084] [Regarding the time T(hr) during which the oxidation reaction was performed]
[0085] In the present embodiment, the oxidation reaction time T(hr) is determined at a specific time of 300 hours or more and 30,000 hours or less, preferably 800 hours or more and 3,000 hours or less, more preferably 1,000 hours or more and 1,500 hours or less, and most preferably 1,300 hours.
[0086] However, as a characteristic of the catalyst of the present embodiment, it is particularly desirable that Q1 is 16 or less at any time between 300 hours and 30,000 hours. In addition, when substituting into the above formula, it is preferable to calculate with two significant figures.
[0087] The catalyst of the present embodiment preferably has a peak at 2θ = 27.4 ± 0.2° in addition to the peak in the X-ray diffraction pattern obtained using CuKα rays as an X-ray source. Furthermore, it is an even more preferable catalyst when the peak intensity is within a specific range. If the peak intensity is denoted as S3 as shown below, its lower limit is, in order of preference, 11.0, 11.5, 12.0, and 12.2 is the most preferable, and its upper limit is, in order of preference, 14.0, 13.0, 12.5, and 12.4 is the most preferable. That is, the preferred range for S3 is 11.0 or higher and 14.0 or lower, and the most preferred range is 12.2 or higher and 12.4 or lower.
[0088] S3 = (peak intensity value at 2θ = 27.4 ± 0.2°) ÷ (peak intensity value at 2θ = 26.5 ± 0.2°) × 100
[0089] In this embodiment, the effect of the catalyst can be clearly demonstrated by evaluating and comparing the catalyst before the oxidation reaction and the catalyst after the oxidation reaction under the same evaluation conditions. Regarding the evaluation conditions, any conditions may be used, but the propylene space velocity is 300 hr -1 It is preferable to evaluate under larger conditions, as this makes it easier to detect differences before and after the oxidation reaction.
[0090] Propylene space velocity 300hr -1 When evaluating under the above conditions, it is desirable to use a small-scale reactor to facilitate evaluation. When changing the reactor, when discharging the catalyst from the reaction tube to obtain the catalyst after the oxidation reaction, it is preferable to divide the reaction tube into three or more sections along the length, take equal samples from each position, mix them, and then perform the evaluation.
[0091] [Regarding the composition of the catalytic active ingredient]
[0092] The catalytic active component included in the catalyst of the present embodiment preferably has a composition represented by the following formula (A).
[0093] Mo a1 Bi b1 Ni c1 Co d1 Fe e1 X f1 Y g1 Z h1 O i1 ···(A)
[0094] (In the formula, Mo, Bi, Ni, Co, and Fe represent molybdenum, bismuth, nickel, cobalt, and iron, respectively; X represents at least one element selected from tungsten, antimony, tin, zinc, chromium, manganese, magnesium, silicon, aluminum, cerium, and titanium; Y represents at least one element selected from sodium, potassium, cesium, rubidium, and thallium; Z represents at least one element selected from elements other than Mo, Bi, Ni, Co, Fe, X, and Y, belonging to Groups 1 through 16 of the periodic table; a1, b1, c1, d1, e1, f1, g1, h1, and i1 represent the number of atoms of molybdenum, bismuth, nickel, cobalt, iron, X, Y, Z, and oxygen, respectively; and when a1 = 12, 0 < b1 ≤ 7, 0 ≤ c1 ≤ 10, 0 < d1 ≤ 10, 0<c1+d1≤20, 0≤e1≤5, 0≤f1≤2, 0≤g1≤3, 0≤h1≤5, and i1=a value determined by the oxidation state of each element.
[0095] In the above formula (A), the preferred range of b1 to i1 is as follows.
[0096] The lower limit of b1 is 0.2, 0.5, 0.7, and 0.8 in order of preference, and most preferably 0.9, and the upper limit of b1 is 5, 3, 2, 1.6, 1.4, and 1.2 in order of preference, and most preferably 1.1. That is, the most preferred range of b1 is 0.9≤b1≤1.1.
[0097] The lower limit of c1 is, in order of preference, 1, 2, 2.5, 2.8, 3.0, most preferably 3.1, and the upper limit of c1 is, in order of preference, 5, 4, 3.8, 3.6, 3.4, most preferably 3.2. That is, the most preferred range of c1 is 3.1≤c1≤3.2.
[0098] The lower limit of d1 is, in order of preference, 3, 4, 5, 5.3, 5.5, 5.7, most preferably 5.8, and the upper limit of d1 is, in order of preference, 8, 7, 6.5, 6.3, 6.1, most preferably 6.0. That is, the most preferred range of d1 is 5.8≤d1≤6.0.
[0099] The lower limit of e1 is, in order of preference, 0.5, 1, 1.2, and 1.4, most preferably 1.5, and the upper limit of e1 is, in order of preference, 4, 3, 2.5, 2, and 1.8, most preferably 1.7. That is, the most preferred range of e1 is 1.5≤e1≤1.7.
[0100] The upper limits of f1 are 8, 7, 6, 5, 3, and 2 in order of preference. The most desirable range of f1 is 0≤f1≤2.
[0101] The lower limit of g1 is, in order of preference, 0, 0.02, 0.04, and 0.06, most preferably 0.07, and the upper limit of g1 is, in order of preference, 1.5, 1, 0.5, 0.2, and 0.15, most preferably 0.10. That is, the most preferred range of g1 is 0.07≤g1≤0.10.
[0102] The upper limits of h1 are 8, 7, 6, and 5 in order of preference. That is, the most desirable range of h1 is 0≤h1≤5.
[0103] In addition, it is preferable that Y contains two or fewer types, and it is particularly preferable that it contains one type. In addition, it is particularly preferable that f1 and h1 are 0.
[0104] [About Damji]
[0105] A catalyst in which a pre-calcined powder, prepared by pre-calcining a catalytic active component after preparation, is supported on an inert carrier is particularly effective as a catalyst of the present embodiment.
[0106] As the material of the inert carrier, known materials such as alumina, silica, titania, zirconia, niobia, silica alumina, silicon carbide, carbides, and mixtures thereof may be used. Additionally, there are no specific restrictions on the particle size, water absorption rate, mechanical strength, the degree of crystallization of each crystal phase, or the mixing ratio thereof, and an appropriate range should be selected considering the performance, moldability, and production efficiency of the final catalyst. The mixing ratio of the carrier and the pre-calcined powder is calculated as the loading ratio from the following formula based on the input mass of each raw material.
[0107] Loading ratio (mass%) = (Mass of pre-fired powder used for molding) / {(Mass of pre-fired powder used for molding) + (Mass of carrier used for molding)} × 100
[0108] The preferred upper limit for the above loading ratio is 80 mass%, and more preferably 60 mass%.
[0109] In addition, the preferred lower limit is 20 mass%, and more preferably 30 mass%. That is, the most preferred range for the loading ratio is 30 mass% or more and 60 mass% or less.
[0110] In addition, as an inert carrier, silica and / or alumina is preferred, and a mixture of silica and alumina is particularly preferred.
[0111] In addition, it is preferable to use a binder during the loading process. Specific examples of binders that can be used include water, ethanol, methanol, propanol, polyhydric alcohols, polyvinyl alcohol as a polymeric binder, and silica sol aqueous solutions as inorganic binders; however, ethanol, methanol, propanol, and polyhydric alcohols are preferred, as are diols such as ethylene glycol or triols such as glycerin, and an aqueous solution of glycerin with a concentration of 5 mass% or more is preferred. By using an appropriate amount of the aqueous glycerin solution, moldability is improved, and a high-performance catalyst with high mechanical strength is obtained. The amount of these binders used is typically 2 to 60 mass parts per 100 mass parts of the pre-calcined powder, but in the case of the aqueous glycerin solution, 10 to 30 mass parts are preferred. During the loading process, the binder and the pre-calcined powder may be supplied to the molding machine alternately or simultaneously.
[0112] As a means of adjusting the above Q1, Q2, Q3, D1, D2, D3 and / or S3, control can be achieved by changing each condition in each manufacturing process described below, but examples include (I) a method of changing the catalyst composition, (II) a method of changing the calcination conditions, (III) a method of changing the cooling conditions after calcination, (IV) a method of controlling so as not to apply mechanical strength to the catalyst and its precursor in the entire process of catalyst manufacturing, (V) a method of using high-purity raw materials, other methods of (VI) to (XI), and a method of combining (I) to (XI). Furthermore, details of other methods (VI) to (XI) will be described below.
[0113] Regarding method (I), in the above composition formula (A), it is a method of adjusting d1 / (b1+c1+e1) to a specific range, the upper limit is 1.25, preferably 1.20, more preferably 1.10, and the lower limit is 0.10, 0.30, 0.50, 0.70, 0.80, 0.90, and 1.00 in order of preference. That is, the most preferred range is 1.00 or more and 1.10 or less.
[0114] In addition, as an upper limit of e1 / b1, it is 1.90, preferably 1.80; as a lower limit of e1 / b1, in order of preference, it is 0.10, 0.50, 1.00, 1.40, 1.50; as an upper limit of d1 / b1, in order of preference, it is 9.0, 8.0, 7.0, 6.0; as a lower limit of d1 / b1, in order of preference, it is 2.0, 3.0, 4.0, 5.0, 5.5; as an upper limit of c1 / e1, in order of preference, it is 4.0, 3.0, 2.5; as a lower limit of c1 / e1, in order of preference, it is 1.5, 1.7, 1.9; as an upper limit of c1 / d1, in order of preference, it is 2.0, 1.0, 0.8; and as a lower limit of c1 / d1, in order of preference, 0.4 and 0.5, and in order of preference as upper limits of g1 / d1 are 0.20, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, and 0.10; in order of preference as lower limits of g1 / d1 are 0.01, 0.02, 0.03, 0.04, and 0.05; in order of preference as upper limits of g1 / c1 are 0.041, 0.039, 0.037, 0.035, 0.033, 0.031, 0.029, 0.025, and 0.023; and in order of preference as lower limits of g1 / c1 are 0.017, 0.019, and 0.021. Additionally, in the above composition formula (A), the lower limit of c1+d1+e1 is 7.0, 7.5, 8.0, 8.5, 9.0, and 9.5 in order of preference, the upper limit of c1+d1+e1 is 13.0, 12.5, 12.0, 11.5, 11.0, and 10.5 in order of preference, the lower limit of b1+c1+d1+e1 is 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, and 11.0 in order of preference, and the upper limit of b1+c1+d1+e1 is 14.0, 13.5, 13.0, 12.5, 12.0, and 11.5 in order of preference.
[0115] Regarding method (II), the pre-firing and main firing described below, and both thereof, are at a temperature of 200°C or higher and 600°C or lower, preferably 300°C or higher and 550°C or lower, more preferably 460°C or higher and 550°C or lower, and the time is 0.5 hours or longer, preferably 1 hour or longer and 40 hours or lower, more preferably 2 hours or longer and 15 hours or lower, most preferably 2 hours or longer and 9 hours or lower, and the atmosphere is at an oxygen concentration of 0 volume% or higher and 40 volume% or lower, preferably 5 volume% or higher and 30 volume% or lower, more preferably 10 volume% to 25 volume%, most preferably an air atmosphere.
[0116] Regarding method (III), the rate of temperature reduction of the catalyst surface from the maximum temperature reached during the calcination process (preliminary calcination temperature or main calcination temperature) to room temperature in the preliminary calcination and the main calcination described below, and in both thereof, is 1°C / min or more and 200°C / min or less, preferably 5°C / min or more and 150°C / min or less, more preferably 10°C / min or more and 120°C / min or less, and most preferably 50°C / min or more and 100°C / min or less. To achieve the aforementioned range of temperature reduction rates, methods of temperature reduction generally adopted industrially, such as exposing the catalyst after calcination removed from the calcination furnace to a mist of an inert atmosphere or an inert solvent, or rapidly moving the catalyst after calcination into a room that has been sufficiently cooled beforehand, are all within the scope of the present invention.
[0117] Regarding method (IV), it is a method of controlling so as not to apply mechanical shock and shear stress, etc. to the catalyst precursor and / or granules formed in each process described later, and the preferred range of mechanical shock and shear stress, etc. is controlled to be 100 kgf or less, preferably 50 kgf or less, more preferably 20 kgf or less, even more preferably 10 kgf or less, and most preferably 5 kgf or less.
[0118] Regarding method (V), the details thereof are not required as long as the method uses raw materials of reagent grade high purity, but for example, the content of sulfur and its compounds, lithium, halogen and its compounds, and lead is 10,000 mass ppm or less, preferably 1,000 mass ppm or less, more preferably 100 mass ppm or less, most preferably 10 mass ppm or less.
[0119] Regarding method (VI), as described below, a method can be used in which the catalyst precursor is first obtained as granules and then molded. By obtaining the catalyst precursor as granules, each component of the catalyst can be manufactured more uniformly.
[0120] Regarding method (VII), in the catalyst combination process described later, the method controls the mixing, reaction, slurrying, and residence time of the cobalt raw material and the nickel raw material in the combination vessel to be as short as possible. More specifically, the method shortens the residence time when the metal salt raw material, excluding molybdenum or alkali metals, is absent from the combination vessel and the cobalt raw material and the nickel raw material are present, or when the pH in the combination vessel takes a specific range and the residence time when the cobalt raw material and the nickel raw material are present. The residence time is preferably 24 hours, more preferably 1 hour, more preferably 30 minutes, and most preferably 10 minutes. The pH range is 1 or higher and 14 or lower, preferably 2 or higher and 10 or lower, more preferably 2 or higher and 8 or lower, and most preferably 3 or higher and 7 or lower. The same applies to the iron raw material and the bismuth raw material, and the molybdenum raw material and the bismuth raw material.
[0121] Regarding method (VIII), in the catalyst combination process described below, when each raw material is introduced, the required amount is not introduced all at once, but is introduced in two or more divided portions. After introducing the divided raw material once, a certain interval is provided between introducing the next raw material, and the time is preferably 5 seconds or more and 1 hour or less, more preferably 30 seconds or more and 45 minutes or less, even more preferably 1 minute or more and 30 minutes or less, and most preferably 3 minutes or more and 15 minutes or less. The number of divisions of a single raw material is preferably 2 or more, more preferably 3 or more, even more preferably 4 or more, and most preferably 5 or more. In the series of combination processes, there may be many raw materials to be divided, each raw material may be divided individually, may be divided after being mixed together as described below, or the individually divided ones may be introduced alternately.
[0122] Regarding method (IX), in the catalyst combination process described below, when preparing a suspended slurry by mixing and stirring the aqueous solutions of each raw material, the addition time of the two or more aqueous solutions used for mixing is preferably 1 second or more and within 30 minutes, more preferably 10 seconds or more and within 20 minutes, even more preferably 30 seconds or more and within 5 minutes, and most preferably 1 minute or more and within 5 minutes.
[0123] Regarding method (X), in the catalyst combination process described below, the transfer time from preparing the final suspended slurry to the drying process of the next process is preferably 10 seconds or more and within 1 hour, more preferably 30 seconds or more and within 10 minutes, and most preferably 1 minute or more and within 5 minutes.
[0124] Regarding method (XI), in the catalyst combination process described below, an organic material is added either before or after each raw material is added. The lower limit of the amount added relative to the molybdenum raw material is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, even more preferably 0.1 mol% or more, and most preferably 1 mol% or more. The upper limit of the amount added is preferably 100 mol% or less, more preferably 90 mol% or less, even more preferably 80 mol% or less, and most preferably 60 mol% or less. Additionally, carboxylic acids or alcohols are preferred as the organic material to be added. Examples include acetic acid, propionic acid, lactic acid, citric acid, stearic acid, oleic acid, ethylenediaminetetraacetic acid, methanol, ethanol, propanol, ethylene glycol, glycerin, etc.
[0125] In addition, as described above, the essence of the present invention lies in the fact that the rate of change of the peak intensity of the crystalline phase of α-CoMoO4 per 1,000 hours of the oxidation reaction is below a certain level. Subsequently, along with examining the catalyst composition as described above, devising the conditions for manufacturing unsaturated aldehyde compounds, unsaturated carboxylic acid compounds, or conjugated diene compounds is also useful for maintaining the reaction process stably. That is, the manufacturing conditions may be controlled so that the rate of change of the peak intensity of the crystalline phase of α-CoMoO4 per 1,000 hours of the oxidation reaction is below a certain level. Specifically, (XII) a method for controlling the hot spot temperature of the catalyst layer, (XIII) a method for controlling the oxygen concentration at the outlet of the reaction tube, (XIV) a method for controlling the steam concentration at the inlet of the reaction tube, (XV) a method for controlling the rate of cooling when performing any cooling treatment during the reaction, (XVI) a method for suppressing mechanical shock applied to the catalyst, and a method combining methods (XII) to (XVI).
[0126] Regarding method (XII), the hot spot temperature of the catalyst layer is controlled to 427°C or lower when producing an unsaturated aldehyde compound, an unsaturated carboxylic acid compound, and / or a conjugated diene, and as upper limits, in order of preference, 420°C or lower, 410°C or lower, 400°C or lower, 390°C or lower, and 380°C or lower. That is, most preferably 380°C or lower. In addition, regarding the time for controlling the hot spot temperature, it is 500 hours or less, preferably 300 hours or less, more preferably 200 hours or less, even more preferably 100 hours or less, and most preferably 50 hours or less.
[0127] Regarding method (XIII), the oxygen concentration at the outlet of the reaction tube when producing an unsaturated aldehyde compound, an unsaturated carboxylic acid compound, and / or a conjugated diene is controlled to 4.0 volume% or more, and as a lower limit, preferably 4.3 volume% or more, more preferably 4.5 volume% or more, and most preferably 4.7 volume% or more.
[0128] Regarding method (XIV), the steam concentration at the inlet of the reaction tube when producing an unsaturated aldehyde compound, an unsaturated carboxylic acid compound, and / or a conjugated diene is managed at 30 volume% or less, and as upper limits, in order of preference, 25 volume% or less, 20 volume% or less, 15 volume% or less, 10 volume% or less, and 9 volume% or less. That is, most preferably 9 volume% or less.
[0129] Regarding method (XV), the rate of temperature reduction (rate of cooling) until the temperature of the catalyst itself is lowered to 100°C or lower from the reaction bath temperature is 1°C / min or more and 200°C / min or less, preferably 5°C / min or more and 150°C / min or less, more preferably 10°C / min or more and 120°C / min or less, and most preferably 50°C / min or more and 100°C / min or less. All cooling methods generally adopted industrially to achieve the above-mentioned range of cooling rates fall within the scope of the present invention.
[0130] Regarding method (XVI), in any process from the charging of the catalyst to the reaction, it is a method of controlling so as not to apply mechanical shock and shear stress, etc. to the catalyst itself, and the preferred range of such mechanical shock and shear stress, etc. is controlled to 100 kgf or less, preferably 50 kgf or less, more preferably 20 kgf or less, even more preferably 10 kgf or less, and most preferably 5 kgf or less.
[0131] [Regarding the method of manufacturing the catalyst, etc.]
[0132] Although there are no particular limitations on the starting materials for each element constituting the catalyst of the present embodiment or the pre-calcined powder thereof, for example, as a raw material for the molybdenum component, molybdenum oxide such as molybdenum trioxide, molybdic acid such as molybdic acid, ammonium paramolybdate, ammonium metamolybdate, or salts thereof, heteropoly acids containing molybdenum such as phosphomolybdic acid and silomolybdic acid or salts thereof may be used.
[0133] As raw materials for bismuth components, bismuth salts such as bismuth nitrate, bismuth carbonate, bismuth sulfate, and bismuth acetate, bismuth trioxide, and metallic bismuth can be used. These raw materials can be used in solid form or as aqueous solutions, nitric acid solutions, or slurries of bismuth compounds formed from such aqueous solutions, but it is preferable to use nitrates, their solutions, or slurries formed from such solutions.
[0134] As starting materials for other component elements, it is preferable to use a combination of ammonium salts, nitrates, nitrites, carbonates, carbonates, acetates, chlorides, inorganic acids, salts of inorganic acids, heteropoly acids, salts of heteropoly acids, sulfates, hydroxides, organic acid salts, oxides, or mixtures thereof of metal elements generally used in this type of catalyst, but ammonium salts and nitrates are suitably used.
[0135] Compounds containing these active ingredients may be used alone or in a mixture of two or more. A slurry solution can be obtained by uniformly mixing each active ingredient-containing compound with water. There are no particular restrictions on the amount of water used in the slurry solution, as long as the amount is sufficient to completely dissolve or uniformly mix the total amount of compounds used. The amount of water should be appropriately determined by taking into account the drying method and drying conditions. Typically, the amount of water used is between 100 parts by mass and 2,000 parts by mass per 100 parts by mass of the total mass of the compounds used for slurry preparation. While a large amount of water is acceptable, using an excessive amount presents many disadvantages, such as increased energy costs for the drying process and the inability to achieve complete drying.
[0136] It is preferable that the slurry solution of the source compounds of each of the above-mentioned component elements be prepared by the following methods: (a) a method of mixing all of the above-mentioned source compounds in a batch; (b) a method of mixing all of them in a batch and then aging; (c) a method of mixing in stages; (d) a method of repeating the mixing and aging processes in stages; and a method combining (a) to (d). Here, the term "aging" refers to "an operation in which an industrial raw material or semi-product is treated under specific conditions, such as a certain time or a certain temperature, to acquire or enhance the required physical and chemical properties or to promote the progress of a predetermined reaction." Furthermore, in the present embodiment, the above-mentioned certain time refers to a range of 5 minutes or more and 24 hours or less, and the above-mentioned certain temperature refers to a range of room temperature or higher and below the boiling point of an aqueous solution or an aqueous dispersion. Among these, the method that is desirable in terms of the activity and yield of the catalyst obtained finally is (c) a stepwise mixing method, and even more desirable is a method in which each raw material mixed into the mother liquor stepwise is a fully dissolved solution, and the most desirable method is a method of mixing an alkali metal solution and various mixed solutions of nitrates into a mother liquor in which the molybdenum raw material is mixed or slurried. However, it is not necessary to mix all the catalyst constituent elements in this process, and some of the elements or some amounts thereof may be added in a subsequent process.
[0137] In this embodiment, there are no particular restrictions on the shape of the stirring blades of the stirrer used when mixing essential active ingredients, and any stirring blade such as propeller blades, turbine blades, paddle blades, inclined paddle blades, screw blades, anchor blades, ribbon blades, large grid blades, etc., may be used in a single stage, or in two or more stages of the same blade or different blades in the vertical direction. In addition, baffles may be installed inside the reaction vessel as needed.
[0138] Next, the slurry obtained in this manner is dried. There are no particular restrictions on the drying method as long as it allows the slurry to be completely dried, but examples include drum drying, freeze drying, spray drying, and evaporative drying. Among these, in the present embodiment, spray drying, which can dry the slurry into powder or granules in a short time, is particularly preferred. The drying temperature of the spray drying varies depending on the concentration of the slurry, the liquid delivery speed, etc., but generally, the temperature at the outlet of the dryer is 70°C or higher and 150°C or lower.
[0139] By pre-calcining the catalyst precursor obtained as described above, and then subjecting it to molding and main calcination, it is possible to control and maintain the molded shape, and a catalyst with particularly excellent mechanical strength for industrial use can be obtained, and stable catalyst performance can be exhibited.
[0140] For molding, either a supporting molding method in which the material is supported on a carrier such as silica, or a non-supporting molding method in which a carrier is not used, may be employed. Specific molding methods include, for example, tablet compression, press molding, extrusion molding, and granulation molding. Regarding the shape of the molded product, for example, a cylindrical shape, a ring shape, or a spherical shape can be appropriately selected considering operating conditions; however, it is preferable to use a supported catalyst having an average particle size of 3.0 mm or more and 10.0 mm or less, preferably 3.0 mm or more and 8.0 mm or less, in which a catalytic active component is supported on a spherical carrier, particularly an inert carrier such as silica or alumina. As for the supporting method, the electric granulation method, the method using a centrifugal flow coating device, and the wash coat method are widely known, and there are no particular limitations as long as the method can uniformly support the pre-calcined powder on the carrier; however, considering the manufacturing efficiency of the catalyst, the electric granulation method is preferred. Specifically, the method involves a device having a flat or uneven disc at the bottom of a fixed cylindrical container, in which the disc is rotated at high speed to vigorously stir a carrier placed inside the container through the repetition of rotational and orbital motions of the carrier itself, and then adding a pre-calcined powder to support the powder components on the carrier. Furthermore, it is preferable to use a binder during the support process. Specific examples of binders that can be used include water, ethanol, methanol, propanol, polyhydric alcohols, polyvinyl alcohol as a polymeric binder, and silica sol aqueous solutions as inorganic binders; however, ethanol, methanol, propanol, and polyhydric alcohols are preferred, diols such as ethylene glycol or triols such as glycerin are more preferred, and an aqueous solution of glycerin with a concentration of 5 mass% or more is even more preferred. By using an appropriate amount of an aqueous glycerin solution, good moldability is achieved, and a high-performance catalyst with high mechanical strength is obtained.The amount of these binders used is typically 2 to 60 parts by mass per 100 parts by mass of pre-calcined powder, but in the case of an aqueous glycerin solution, 15 to 50 parts by mass is preferred. During loading, the binder and the pre-calcined powder may be supplied to the molding machine alternately or simultaneously. In addition, during molding, a small amount of known additives, such as graphite or talc, may be added. Furthermore, molding aids, pore-forming agents, and carriers added during molding are all not considered as constituent elements of the active ingredient in this embodiment, regardless of whether they have activity in the sense of converting the raw material into any other product.
[0141] The preliminary calcination method, preliminary calcination conditions, or main calcination method and main calcination conditions are not particularly limited, and known processing methods and conditions may be applied. The preliminary calcination or main calcination is typically carried out under the flow of an oxygen-containing gas, such as air, or under the flow of an inert gas, at a temperature of 200°C or higher and 600°C or lower, preferably 300°C or higher and 550°C or lower, for 0.5 hours or more, preferably 1 hour or more and 40 hours or less. Here, an inert gas refers to a gas that does not reduce the reaction activity of the catalyst, and specifically, examples include nitrogen, carbon dioxide, helium, argon, etc. Furthermore, depending on the reaction conditions when producing unsaturated aldehydes and / or unsaturated carboxylic acids using the catalyst, the optimal conditions, particularly for the main calcination, differ. Since it is known to those skilled in the art to change process parameters of the main calcination process, such as the oxygen content in the atmosphere, the maximum temperature reached, and the calcination time, such changes are considered to fall within the scope of the present invention. In addition, the main calcination process shall be carried out after the aforementioned preliminary calcination process, and the maximum temperature reached in the main calcination process (main calcination temperature) shall be higher than the maximum temperature reached in the aforementioned preliminary calcination process (preliminary calcination temperature). There are no particular restrictions on the calcination method, such as fluidized bed, rotary kiln, muffle furnace, or tunnel calcination furnace, and an appropriate range must be selected considering the final catalyst performance, mechanical strength, moldability, and production efficiency.
[0142] The catalyst of the present embodiment is preferably used as a catalyst for producing unsaturated aldehyde compounds, unsaturated carboxylic acid compounds, or conjugated diene compounds, more preferably as a catalyst for producing unsaturated aldehyde compounds, and particularly preferably as a catalyst for producing acrolein from propylene. In processes of exothermic reactions such as producing unsaturated aldehyde compounds, unsaturated carboxylic acid compounds, or conjugated diene compounds, it is known to those skilled in the art that different catalyst species are packed in multiple layers from the reaction tube inlet side toward the reaction tube outlet side to increase activity, for the purpose of preventing the catalyst itself from deteriorating due to the exothermic reaction generated by the reaction in the actual plant. The catalyst of the present embodiment may be used at the reaction tube inlet side, the reaction tube outlet side, or any of the intermediate catalyst layers, but it is most preferable to use it, for example, at the outermost outlet side of the reaction tube, that is, in the catalyst with the highest activity among all catalyst layers within the reaction tube. In addition, regarding multilayer filling, two-layer or three-layer filling is a particularly desirable type.
[0143] [Regarding the second stage catalyst]
[0144] When the catalyst of the present embodiment is used as a first-stage catalyst, that is, as a catalyst for producing an unsaturated aldehyde compound, a second-stage oxidation reaction can be performed to obtain an unsaturated carboxylic acid compound.
[0145] In this case, as the second stage catalyst, the catalyst of the present embodiment may be used, but preferably, it is a catalyst comprising a catalytic active component represented by the following formula (B).
[0146] Mo 12 V a2 W b2 Cu c2 Sb d2 X2 e2 Y2 f2 Z2 g2 O h2 ···(B)
[0147] (In the formula, Mo, V, W, Cu, Sb, and O represent molybdenum, vanadium, tungsten, copper, antimony, and oxygen, respectively; X2 represents at least one element selected from the group consisting of alkali metals and thallium; Y2 represents at least one element selected from the group consisting of magnesium, calcium, strontium, barium, and zinc; and Z2 represents at least one element selected from the group consisting of niobium, cerium, tin, chromium, manganese, iron, cobalt, samarium, germanium, titanium, and arsenic, respectively. Additionally, a2, b2, c2, d2, e2, f2, g2, and h2 represent the atomic ratios of each element, and for 12 molybdenum atoms, a2 is 0 < a2 ≤ 10, b2 is 0 ≤ b2 ≤ 10, c2 is 0 < c2 ≤ 6, d2 is 0 < d2 ≤ 10, and e2 is 0≤e2≤0.5, f2 represents 0≤f2≤1, and g2 represents 0≤g2<6. Also, h2 is the number of oxygen atoms required to satisfy the valence of each of the above components.)
[0148] In preparing a catalyst containing a catalytic active component represented by the above formula (B), a method generally known as a method for preparing this type of catalyst, for example, an oxide catalyst, a heteropoly acid, or a salt thereof, may be employed. The raw materials that can be used when preparing the catalyst are not particularly limited and various materials may be used. For example, molybdenum oxides such as molybdenum trioxide, molybdic acid, molybdic acid such as ammonium molybdate or its salt, heteropoly acids containing molybdenum such as phosphomolybdic acid and silomolybdic acid or their salts may be used. There are no particular restrictions on the raw materials for the antimony component, but antimony trioxide or antimony acetate is preferred. As raw materials for other elements such as vanadium, tungsten, and copper, their respective nitrates, sulfates, carbonates, phosphates, organic acid salts, halides, hydroxides, oxides, metals, etc., may be used.
[0149] Compounds containing these active ingredients may be used alone or in combination of two or more.
[0150] Next, the slurry obtained above is dried to form a solid catalyst active component. There are no particular restrictions on the drying method as long as it can completely dry the slurry, but examples include drum drying, freeze drying, spray drying, and evaporation drying; spray drying, which can dry the slurry into powder or granules in a short time, is preferred. The drying temperature of the spray drying varies depending on the concentration of the slurry, the liquid delivery speed, etc., but generally, the temperature at the outlet of the dryer is 70 to 150°C. In addition, it is preferable to dry the slurry so that the average particle size of the dried slurry obtained at this time is 10 to 700 μm.
[0151] The solid of the second stage catalyst active component obtained as described above can be provided directly to the coating mixture, but it is preferable to calcin it as this may improve moldability. The calcination method and conditions are not particularly limited, and known processing methods and conditions may be applied. The optimal calcination conditions vary depending on the catalyst raw material used, catalyst composition, preparation method, etc., but the calcination temperature is typically 100 to 350°C, preferably 150 to 300°C, and the calcination time is 1 to 20 hours. In addition, calcination is usually performed under an air atmosphere, but it may also be performed under an inert gas atmosphere such as nitrogen, carbon dioxide, helium, or argon, or, if necessary, additional calcination may be performed under an air atmosphere after calcination under an inert gas atmosphere. It is preferable that the solid obtained after calcination in this way be ground before molding. There are no particular restrictions on the grinding method, but a ball mill may be used.
[0152] In addition, the compound containing the active ingredient when preparing the second stage slurry above does not necessarily have to contain all the active ingredients, and some of the ingredients may be used before the molding process below.
[0153] There are no particular restrictions on the shape of the second-stage catalyst mentioned above, and it is formed into a columnar shape, tablet, ring shape, spherical shape, etc., to minimize pressure loss of the reaction gas during the oxidation reaction. Among these, it is particularly desirable to support a solid catalyst active component on an inert carrier to form a supported catalyst, as this allows for improved selectivity and the removal of reaction heat. The electric assembly method described below is preferred for this support. This method involves, for example, a device having a flat or uneven disc at the bottom of a fixed container, in which the disc is rotated at high speed to vigorously agitate the carrier within the container through repeated rotational and orbital motions, and then supporting the carrier with a binder, a solid catalyst active component, and, if necessary, other additives such as molding aids or strength enhancers. The method of adding the binder may be arbitrarily adopted, such as 1) mixing it in advance with the above-mentioned supporting mixture, 2) adding it simultaneously with adding the supporting mixture into the fixed container, 3) adding it after adding the supporting mixture into the fixed container, 4) adding it before adding the supporting mixture into the fixed container, or 5) dividing the supporting mixture and the binder separately and adding the total amount by appropriately combining methods 2) to 4). Among these, regarding method 5), it is preferable to control the addition speed using an auto feeder, for example, so that there is no adhesion of the supporting mixture to the wall of the fixed container or aggregation of the supporting mixtures, and a predetermined amount is supported on the carrier. Examples of binders include water, ethanol, polyhydric alcohols, polyvinyl alcohol of polymeric binders, celluloses such as crystalline cellulose, methylcellulose, and ethylcellulose, and aqueous silica sol solutions of inorganic binders, but celluloses and diols such as ethylene glycol or triols such as glycerin are preferred, and an aqueous solution of glycerin with a concentration of 5 mass% or more is particularly preferred.The amount of these binders used is typically 2 to 60 parts by mass, preferably 10 to 50 parts by mass, per 100 parts by mass of the supporting mixture.
[0154] Specific examples of the carriers in the above-mentioned support include spherical carriers with a diameter of 1 to 15 mm, preferably 2.5 to 10 mm, such as silicon carbide, alumina, silica alumina, mullite, and alundum. These carriers are typically used having a porosity of 10 to 70%. The ratio of the carrier to the supporting mixture is typically used in an amount such that the supporting mixture / (supporting mixture + carrier) = 10 to 75 mass%, preferably 15 to 60 mass%. When the ratio of the supporting mixture is high, the reaction activity of the supported catalyst increases, but the mechanical strength tends to decrease. Conversely, when the ratio of the supporting mixture is low, the mechanical strength increases, but the reaction activity tends to decrease. In addition, molding aids used as needed in the above-mentioned method include silica gel, diatomaceous earth, and alumina powder. The amount of molding aid used is typically 1 to 60 mass parts per 100 mass parts of the solid catalyst active component. In addition, if necessary, using inorganic fibers (e.g., ceramic fibers or whiskers, etc.) that are inert to the catalytic active component solid and reaction gas as strength enhancers is useful for improving the mechanical strength of the catalyst, and glass fibers are preferred. The amount of these fibers used is typically 1 to 30 parts by mass per 100 parts by mass of the catalytic active component solid. Furthermore, in the molding of the catalyst in the first stage, the added molding aid, pore-forming agent, and carrier are all not considered as constituent elements of the active component in this embodiment, regardless of whether they have activity in the sense of converting the raw material into any other product.
[0155] The supported catalyst obtained as described above can be provided as is for a gas-phase contact oxidation reaction as a catalyst, but it is preferable to calcinate it as this may improve catalytic activity. The calcination method and calcination conditions are not particularly limited, and known treatment methods and conditions may be applied. The optimal calcination conditions vary depending on the catalyst raw material used, catalyst composition, preparation method, etc., but the calcination temperature is typically 100 to 450°C, preferably 270 to 420°C, and the calcination time is 1 to 20 hours. In addition, calcination is usually performed under an air atmosphere, but it may also be performed under an inert gas atmosphere such as nitrogen, carbon dioxide, helium, or argon, and if necessary, additional calcination may be performed under an air atmosphere after calcination under an inert gas atmosphere.
[0156] When the catalyst of the present embodiment is used in a reaction to produce corresponding unsaturated aldehydes and unsaturated carboxylic acids using propylene, isobutylene, t-butyl alcohol, etc. as raw materials, particularly in a reaction to produce acrolein and acrylic acid by gas-phase contact oxidation of propylene with molecular oxygen or a molecular oxygen-containing gas, the catalyst activity and yield can be improved, which is highly effective in improving the price competitiveness of the product compared to known methods. In addition, an improvement effect can be expected in the process stability of partial oxidation reactions involving exothermic reactions, such as the reduction of hot spot temperature. Furthermore, the catalyst of the present embodiment is also effective in reducing by-products that have adverse effects on the environment or the quality of the final product, such as carbon monoxide (CO), carbon dioxide (CO2), acetaldehyde, acetic acid, and formaldehyde.
[0157] The catalyst of the present embodiment obtained in this way can be used, for example, to produce acrolein and / or acrylic acid by gas-phase contact oxidation of propylene using a molecular oxygen-containing gas. In the manufacturing method of the present embodiment, the method of circulating the raw material gas may be a conventional single-flow method or a recycling method, and can be carried out under generally used conditions and is not particularly limited. For example, a mixed gas comprising propylene as a starting material at room temperature in an amount of 1 to 10 volume%, preferably 4 to 9 volume%; molecular oxygen in an amount of 3 to 20 volume%, preferably 4 to 18 volume%; water vapor in an amount of 0 to 60 volume%, preferably 4 to 50 volume%; and an inert gas such as carbon dioxide or nitrogen in an amount of 20 to 80 volume%, preferably 30 to 60 volume%, is filled into a reaction tube and placed on the catalyst of the present embodiment at 250 to 450°C, under a pressure of atmospheric pressure to 10 atmospheres, at a space velocity of 300 to 5000 h -1 It is introduced to perform the reaction.
[0158] In the present invention, improvement of catalytic activity refers to a higher conversion rate of raw materials when a catalytic reaction is performed at the same reaction bath temperature and compared, unless otherwise specifically mentioned.
[0159] In the present invention, a high yield refers to a high total yield of the corresponding unsaturated aldehyde and / or unsaturated carboxylic acid when an oxidation reaction is performed using propylene, isobutylene, t-butyl alcohol, etc., as raw materials, unless otherwise specifically stated. Also, unless otherwise specifically stated, yield refers to the effective yield described below.
[0160] In the present invention, the constituent elements of the catalytic active component refer to all elements used in the catalyst manufacturing process unless specifically mentioned otherwise, but raw materials and their constituent elements that are lost, sublimated, volatilized, or burned at temperatures below the maximum temperature of the calcination process are not included in the constituent elements of the catalytic active component. In addition, elements constituting silicon and other inorganic materials included in the molding aid or carrier in the molding process are not included as constituent elements of the catalytic active component.
[0161] In the present invention, the hot spot temperature is the highest temperature of the temperature distribution within the catalyst packing layer measured by installing a thermocouple in the direction of the long axis within the multi-tube reaction tube, and the reaction bath temperature is the set temperature of the heat transfer medium used for the purpose of cooling the heat generated by the reaction tube. There are no particular limitations on the number of points for measuring the temperature distribution, but for example, the catalyst packing length is divided evenly into 10 to 1000. Furthermore, for the measurement of the hot spot temperature, it is known to those skilled in the art to install a temperature sill in the direction of the long axis of the reaction tube and install a thermocouple therein for the purpose of stabilizing the measurement by the thermocouple. There are no limitations on the outer diameter of this temperature sill, but for example, it is preferably 7 mm or less, more preferably 6 mm or less, and even more preferably 3.5 mm or less. There are no limitations on the outer diameter of the thermocouple, but for example, it is preferably 6 mm or less, more preferably 4 mm or less, and even more preferably 3 mm or less.
[0162] In the present invention, unsaturated aldehydes and unsaturated aldehyde compounds are organic compounds having at least one double bond and at least one aldehyde within a molecule, examples of which are acrolein and methacrolein. In the present invention, unsaturated carboxylic acids and unsaturated carboxylic acid compounds are organic compounds having at least one double bond and at least one carboxyl group or its ester group within a molecule, examples of which are acrylic acid, methacrylic acid, and methyl methacrylate. In the present invention, conjugated dienes are dienes that are chemically conjugated by removing a double bond by a single single bond, examples of which are 1,3-butadiene.
[0163] The catalyst of the present invention also has the advantages of (i) reduction of the hot spot temperature and (ii) stable activity even when the reaction bath temperature is low.
[0164] Examples
[0165] The present invention will be explained in more detail below through examples. In addition, in the examples, the raw material conversion rate, effective selectivity, butadiene selectivity, loading rate, and outlet oxygen concentration were calculated according to the following formula.
[0166] Feed Conversion Rate (%) = (Moles of reacted propylene, t-butyl alcohol, isobutylene, or butene) / (Moles of supplied propylene, t-butyl alcohol, isobutylene, or butene) × 100
[0167] Effective selectivity (%) = (Total moles of acrolein and acrylic acid produced, or Total moles of methacrolein and methacrylic acid produced) / (Moles of reacted propylene, t-butyl alcohol, or isobutylene) × 100
[0168] Butadiene selectivity (%) = (Total moles of butadiene produced) / (Moles of butene reacted) × 100
[0169] Loading ratio (mass%) = (Mass of pre-fired powder used for molding) / {(Mass of pre-fired powder used for molding) + (Mass of carrier used for molding)} × 100
[0170] Outlet oxygen concentration (volume %) = (Moles of oxygen at the reaction tube outlet) / (Moles of total gas containing water vapor at the reaction tube outlet) × 100
[0171] In addition, the measurement of the X-ray diffraction (XRD) angle (2θ) was performed using Ultima IV manufactured by Rigaku Co., Ltd. under the conditions of X-ray CuKα (λ = 0.154 nm), output 40 kV, 30 mA, measurement range 10 to 60°, and measurement speed 10° per minute. Furthermore, the firing time described in each of the following examples, the heating time and the cooling time refer to the retention time from the time each firing temperature of the non-incorporated material is reached.
[0172] In addition, the aging treatment described below means filling a reaction tube of a specified diameter with a catalyst, flowing propylene at a specified flow rate, and carrying out an oxidation reaction for a specified period. At this time, the temperature of the reaction bath is any temperature, but the lower limit is 300°C and the upper limit is a temperature at which the temperature of the catalyst layer inside the reaction tube becomes 450°C or lower.
[0173] [Example 1]
[0174] 100 parts by mass of ammonium heptamolybdate were completely dissolved in 380 parts by mass of pure water heated to 60°C (mother liquor 1). Next, 0.37 parts by mass of potassium nitrate were dissolved in 3.3 parts by mass of pure water and added to mother liquor 1. Next, 31 parts by mass of ferric nitrate, 81 parts by mass of cobalt nitrate, and 44 parts by mass of nickel nitrate were dissolved in 83 parts by mass of pure water heated to 60°C and added dropwise to mother liquor 1. Subsequently, 23 parts by mass of bismuth nitrate were dissolved in an aqueous nitric acid solution prepared by adding 5.8 parts by mass of nitric acid (60% by mass) to 24 parts by mass of pure water heated to 60°C and added dropwise to mother liquor 1. This mother liquor 1 was dried by the spray drying method, and the obtained dry powder was pre-calcined at 440°C for 4 hours. To the pre-calcined powder obtained in this way (atomic ratio calculated from input raw materials: Mo:Bi:Fe:Co:Ni:K = 12:1.0:1.6:5.9:3.2:0.080), 5 mass% of crystalline cellulose was added and thoroughly mixed. Then, using a 33 mass% glycerin solution as a binder, the powder was supported and molded into a spherical shape on an inert carrier such that the loading rate was 50 mass%. The spherical molded product with a particle size of 5.3 mm obtained in this way was subjected to main calcination at 510°C for 4 hours to obtain catalyst 1-1. The X-ray diffraction angle (2θ) of catalyst 1-1 was measured. Also, S3 was 12.3.
[0175] Catalyst 1-1 was packed into a stainless steel reaction tube with an inner diameter of 25 mm, a propylene concentration of 8 vol%, and a propylene space velocity of 160 hr for the total catalyst in the reaction tube. -1 An aging treatment was performed for 1300 hours under the following conditions. During the aging treatment, the maximum temperature of the catalyst layer inside the reaction tube was 444°C, and the minimum oxygen concentration of the gas at the reaction tube outlet was 4.8 volume%. Afterward, the catalyst was removed from the reaction tube to obtain catalyst 1-2. The X-ray diffraction angle (2θ) of catalyst 1-2 was measured.
[0176] [Example 2]
[0177] 100 parts by mass of ammonium heptamolybdate were completely dissolved in 380 parts by mass of pure water heated to 60°C (mother liquor 1). Next, 0.17 parts by mass of potassium nitrate were dissolved in 1.5 parts by mass of pure water and added to mother liquor 1. Next, 38 parts by mass of ferric nitrate, 89 parts by mass of cobalt nitrate, and 33 parts by mass of nickel nitrate were dissolved in 85 parts by mass of pure water heated to 60°C and added dropwise to mother liquor 1. Subsequently, 21 parts by mass of bismuth nitrate were dissolved in an aqueous nitric acid solution prepared by adding 5.4 parts by mass of nitric acid (60% by mass) to 23 parts by mass of pure water heated to 60°C and added dropwise to mother liquor 1. This mother liquor 1 was dried by the spray drying method, and the obtained dry powder was pre-calcined at 440°C for 4 hours. To the pre-calcined powder obtained in this way (atomic ratio calculated from input raw materials is Mo:Bi:Fe:Co:Ni:K = 12:0.93:2.0:6.5:2.4:0.040), 5 mass% of crystalline cellulose was added and thoroughly mixed. Then, using a 33 mass% glycerin solution as a binder, the powder was supported and molded into a spherical shape on an inert carrier such that the loading rate was 50 mass%. The spherical molded product with a particle size of 5.3 mm obtained in this way was subjected to main calcination at 550°C for 4 hours to obtain catalyst 2-1. The X-ray diffraction angle (2θ) of catalyst 2-1 was measured. Also, S3 was 11.3.
[0178] Catalyst 2-1 was packed into a stainless steel reaction tube with an inner diameter of 25 mm, a propylene concentration of 8 vol%, and a propylene space velocity of 95 hr for the total catalyst in the reaction tube. -1 An aging treatment was performed for 26,000 hours under the conditions. During the aging treatment, the maximum temperature of the catalyst layer inside the reaction tube was 384°C, and the minimum oxygen concentration of the gas at the reaction tube outlet was 3.9 volume%. Afterward, catalyst 2-2 was obtained by removing it from the reaction tube. The X-ray diffraction angle (2θ) of catalyst 2-2 was measured.
[0179] [Example 3]
[0180] 100 parts by mass of ammonium heptamolybdate were completely dissolved in 380 parts by mass of pure water heated to 60°C (mother liquor 1). Next, 0.44 parts by mass of potassium nitrate were dissolved in 4.0 parts by mass of pure water and added to mother liquor 1. Next, 34 parts by mass of ferric nitrate, 71 parts by mass of cobalt nitrate, and 38 parts by mass of nickel nitrate were dissolved in 76 parts by mass of pure water heated to 60°C and added to mother liquor 1. Subsequently, 38 parts by mass of bismuth nitrate were dissolved in an aqueous nitric acid solution prepared by adding 9.9 parts by mass of nitric acid (60% by mass) to 41 parts by mass of pure water heated to 60°C and added to mother liquor 1. This mother liquor 1 was dried by the spray drying method, and the obtained dry powder was pre-calcined at 440°C for 4 hours. To the pre-calcined powder obtained in this way (atomic ratios calculated from input raw materials: Mo:Bi:Fe:Co:Ni:K = 12:1.7:1.8:5.2:2.8:0.095), 5 mass% of crystalline cellulose was added and thoroughly mixed. Then, using a 33 mass% glycerin solution as a binder, the powder was supported and molded into a spherical shape on an inert carrier such that the loading rate was 50 mass%. The spherical molded product with a particle size of 5.3 mm obtained in this way was subjected to main calcination at 530°C for 4 hours to obtain catalyst 3-1. The X-ray diffraction angle (2θ) of catalyst 3-1 was measured. FIG. 1 is a diagram showing the X-ray diffraction pattern of catalyst 3-1. Also, S3 was 12.0.
[0181] Catalyst 3-1 was packed into a stainless steel reaction tube with an inner diameter of 27 mm, a propylene concentration of 8 vol%, and a propylene space velocity of 100 hr for the total catalyst in the reaction tube. -1 Aging treatment was performed for 24,000 hours under the conditions. Afterward, catalyst 3-2 was obtained by removing it from the reaction tube. The X-ray diffraction angle (2θ) of catalyst 3-2 was measured. FIG. 2 is a diagram showing the X-ray diffraction pattern of catalyst 3-2.
[0182] [Comparative Example 1]
[0183] 100 parts by mass of ammonium heptamolybdate were completely dissolved in 380 parts by mass of pure water heated to 60°C (mother liquor 1). Next, 0.46 parts by mass of potassium nitrate were dissolved in 4.1 parts by mass of pure water and added to mother liquor 1. Next, 38 parts by mass of ferric nitrate, 89 parts by mass of cobalt nitrate, and 33 parts by mass of nickel nitrate were dissolved in 85 parts by mass of pure water heated to 60°C and added to mother liquor 1. Subsequently, 16 parts by mass of bismuth nitrate were dissolved in an aqueous nitric acid solution prepared by adding 4.1 parts by mass of nitric acid (60% by mass) to 17 parts by mass of pure water heated to 60°C and added to mother liquor 1. This mother liquor 1 was dried by the spray drying method, and the obtained dry powder was pre-calcined at 440°C for 4 hours. To the pre-calcined powder obtained in this way (atomic ratio calculated from input raw materials: Mo:Bi:Fe:Co:Ni:K = 12:0.7:2.0:6.5:2.4:0.10), 5 mass% of crystalline cellulose was added and thoroughly mixed. Then, using a 33 mass% glycerin solution as a binder, the powder was supported and molded into a spherical shape on an inert carrier such that the loading rate was 50 mass%. The spherical molded product with a particle size of 5.3 mm obtained in this way was subjected to main calcination at 540°C for 4 hours to obtain catalyst 4-1. The X-ray diffraction angle (2θ) of catalyst 4-1 was measured. FIG. 3 is a diagram showing the X-ray diffraction pattern of the catalyst of Comparative Example 1 (catalyst 4-1). Also, S3 was 13.5.
[0184] Catalyst 4-1 was packed into a stainless steel reaction tube with an inner diameter of 25 mm, a propylene concentration of 8 vol%, and a propylene space velocity of 160 hr for the total catalyst in the reaction tube. -1An aging treatment was performed for 1300 hours under the following conditions. During the aging treatment, the maximum temperature of the catalyst layer inside the reaction tube was 444°C, and the minimum oxygen concentration of the gas at the reaction tube outlet was 4.8 volume%. Afterward, catalyst 4-2 was obtained by removing it from the reaction tube. The X-ray diffraction angle (2θ) of catalyst 4-2 was measured. FIG. 4 is a diagram showing the X-ray diffraction pattern of catalyst 4-2.
[0185] Using catalysts 1-1, 2-1, 3-1, and 4-1, and catalysts 1-2, 2-2, 3-2, and 4-2 removed from the reaction tube after aging treatment, the oxidation reaction of propylene was carried out by the following method to determine the raw material conversion rate and effective selectivity. Each catalyst was filled into a stainless steel reaction tube with an inner diameter of 18.4 mm, and a mixed gas with a gas volume ratio of propylene:oxygen:water vapor = 1:1.7:3.0 was introduced at a propylene space velocity of 400 hr⁻¹ relative to the total catalyst in the reaction tube. -1 The oxidation reaction of propylene was carried out by introducing the catalyst. Analysis of the reaction tube outlet gas was performed between 100 and 150 hours from the start of the introduction of propylene. The results of the reaction bath temperature, raw material conversion rate, effective selectivity, and XRD measurements for catalysts 1-1, 2-1, 3-1, and 1-4 are shown in Table 1, and the results of the reaction bath temperature, raw material conversion rate, effective selectivity, and XRD measurements for catalysts 1-2, 2-2, 3-2, and 4-2 are shown in Table 2.
[0186]
[0187]
[0188] Table 3 shows the reduction in effective selectivity per 1000 hours of reaction time, Q1, Q2, Q3, D1, D2, and D3, considering the reaction time T(hr) for the oxidation reaction above.
[0189]
[0190] Although the present invention has been described in detail with reference to specific aspects, it is obvious to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the invention.
[0191] In addition, the present invention is based on Japanese patent application filed on January 10, 2020 (JP 2020-002508), the entirety of which is incorporated by reference. In addition, all references cited herein are incorporated in their entirety.
[0192] (Industrial Applicability)
[0193] When using the catalyst of the present invention to produce unsaturated aldehyde compounds, unsaturated carboxylic acid compounds, or conjugated diene compounds by a partial oxidation reaction, a high selectivity is realized, and as a result, a high yield is expected to be obtained.
Claims
Claim 1 A catalyst for the production of unsaturated aldehyde compounds and unsaturated carboxylic acid compounds, containing molybdenum, bismuth, and cobalt as essential components, wherein the rate of change (Q1) per 1,000 hours of reaction time represented by the following formulas (1) to (4) is 16 or less with respect to the peak intensity at 2θ = 25.3±0.2° in the X-ray diffraction pattern obtained using CuKα rays as an X-ray source. Q1 = {(U1 / F1-1)×100} / T×1000···(1) F1 = (peak intensity value of 2θ = 25.3±0.2° of the catalyst before oxidation reaction) ÷ (peak intensity value of 2θ = 26.5±0.2° of the catalyst before oxidation reaction) × 100···(2) U1 = (peak intensity value of 2θ = 25.3±0.2° of the catalyst after oxidation reaction) ÷ (of the catalyst after oxidation reaction 2θ = peak intensity value of 26.5±0.2° × 100···(3)T = time taken for oxidation reaction (hr)···(4) Claim 2 A catalyst for the production of unsaturated aldehyde compounds and unsaturated carboxylic acid compounds according to claim 1, wherein for the peak intensity of 2θ = 25.3 ± 0.2° in the X-ray diffraction pattern obtained using CuKα rays as an X-ray source, the change amount (D1) per 1000 hours of reaction time represented by the following formula (5) and the above formulas (2) to (4) is 4.1 or less. D1 = (U1 - F1) / T × 1000 ···(5) Claim 3 A catalyst for the production of unsaturated aldehyde compounds and unsaturated carboxylic acid compounds according to claim 1 or 2, wherein the composition of the catalytic active component is represented by the following formula (A). a1 Bi b1 Ni c1 Co d1 Fe e1 X f1 Y g1 Z h1 O i1 ···(A)(wherein, Mo, Bi, Ni, Co, and Fe represent molybdenum, bismuth, nickel, cobalt, and iron, respectively; X represents at least one element selected from tungsten, antimony, tin, zinc, chromium, manganese, magnesium, silicon, aluminum, cerium, and titanium; Y represents at least one element selected from sodium, potassium, cesium, rubidium, and thallium; Z represents at least one element belonging to Groups 1 through 16 of the periodic table and selected from elements other than Mo, Bi, Ni, Co, Fe, X, and Y; a1, b1, c1, d1, e1, f1, g1, h1, and i1 represent the number of atoms of molybdenum, bismuth, nickel, cobalt, iron, X, Y, Z, and oxygen, respectively; and when a1 = 12, 0 < b1 ≤ 7, 0 ≤ c1 ≤ 10, 0<d1≤10, 0<c1+d1≤20, 0≤e1≤5, 0≤f1≤2, 0≤g1≤3, 0≤h1≤5 and, i1 = a value determined by the oxidation state of each element) Claim 4 A catalyst for the production of unsaturated aldehyde compounds and unsaturated carboxylic acid compounds, wherein, in claim 1 or 2, the catalyst is a catalyst in which a catalytic active component is supported on an inert carrier. Claim 5 A catalyst for the production of unsaturated aldehyde compounds and unsaturated carboxylic acid compounds, wherein the inert carrier is silica, alumina, or a mixture thereof, in paragraph 4. Claim 6 delete Claim 7 A method for producing unsaturated aldehyde compounds and unsaturated carboxylic acid compounds using a catalyst described in claim 1 or 2. Claim 8 A method of manufacturing according to claim 7, wherein the unsaturated aldehyde compound is acrolein and the unsaturated carboxylic acid compound is acrylic acid. Claim 9 delete
Citation Information
Patent Citations
Method for producing unsaturated aldehyde and / or unsaturated carboxylic acid
EP2671862A1
Catalyst for manufacturing unsaturated aldehyde and / or unsaturated carboxylic acid, method for manufacturing same, and method for manufacturing unsaturated aldehyde and / or unsaturated carboxylic acid
EP2995375A1
Catalyst for conjugated diolefin production, and method for producing same
KR1020180069052A
Method for producing unsaturated aldehyde and / or unsaturated carboxylic acid
KR1020160032037A